Analisis Kualitas Pelayanan Pajak Kendaraan Bermotor Pada Unit Pel ayanan Pendapatan Daerah Pontianak Wilayah I - Riyanti Herawati (Universitas Muhammadiyah Pontianak, 2015)
The aim of this study was to determine the quality of taxpayer service vehicles on Revenue Services Unit Lagos Region I. The method used in this research is descriptive. Data collection techniques are observation, interviews and questionnaires. The sample of 100 persons of the population in the form of compulsory motor vehicle tax. Sampling technique is purposive. Analysis tool used is Service Quality (SERVQUAL). The analysis showed that the quality of service is not satisfactory for the respondent. It can be seen through a comparison of the scores obtained by the perception of -0.508, while the expectation of which amounted to -0.55.